A NATIONAL STUDY ON THE ANTECEDENTS AND OUTCOMES OF WORK-LIFE BALANCE IN IRAN - Tavassoli, Tara; Sune, Albert (PEOPLE: International Journal of Social Sciences, 2018)
This paper examines the impact of work-life balance (WLB) on individual outcomes of full time employees in Iran. This research aims to identify the influence of WLB on job satisfaction, life satisfaction, and turnover intentions. Moreover, this paper aims to identify the influence of a selected group of antecedents (job autonomy, work demands and supervisor work-family support) on WLB. Structural equation modeling in AMOS is used to analyze data from a sample of 203 full time workers in Iran. Analysis of data reveals positive relationships between WLB and job and life satisfaction while negative relationships between WLB and turnover intentions. The results also show significant relationships with all the studied antecedents of WLB. Job autonomy and supervisor work-family support have a positive relationship with WLB while work demands have a negative relationship with WLB. This is one of the first studies to analyze antecedents and outcomes of WLB in Iran. The results show that WLB is a relevant factor in the Iranian society. Employees that are able to balance all their life roles experience higher satisfaction and have less intention to leave their organization. In addition, the perception of balance is strongly influenced by work and family conditions. These findings align with other national studies in Western countries. Further research is needed to assess other work and non-work conditions that might influence WLB, for example, the role that colleagues, supervisors and HR management play in creating supportive work environments. It would also be valuable to extend the current study to other countries to develop a comparative cross-national research.